Advanced Polymer Nanocomposites II - Liu, Ting-Yu; Cheng, Yu-Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue reprint, "Advanced Polymer Nanocomposites II", addresses high-quality original and review papers, focused on the scientific discussion and practical application in the field of functional polymer nanocomposites, including: (a) optoelectronic materials (papers 1-9); (b) biomedical materials (papers 10-14); and (c) other functional polymer nanocomposites (papers 15-23). We hope that this Special Issue reprint can promote academic research exchanges and identify and respond to tremendous challenges of research in this burgeoning field.